Air pollutants and daily number of admissions to psychiatric emergency services: evidence for detrimental mental health effects of ozone. (2020) - Bernardini, F.; Attademo, L.; Trezzi, R.; Gobbicchi, C.; Balducci, P.M.; Del Bello, V.; Menculini, G.; Pauselli, L.; Piselli, M.; Sciarma, T.; Moretti, P.; Tamantini, A.; et al.
Abstract: Aims: Aim of the current study is to investigate the associations between daily levels of air pollutants (particulate matter, ozone, carbon monoxide, nitrogen dioxide) and daily admissions for mental disorders to the emergency department of two general hospitals in Umbria region (Italy). Methods: We collected data about daily admissions to psychiatric emergency services of two general hospitals, air pollutants' levels and meteorological data for the time period 1 January 2015 until 31 December 2016. We assessed the impact of an increase in air pollutants on the number of daily admissions using a time-series econometric framework. Results: A total of 1860 emergency department admissions for mental disorders were identified. We observed a statistically significant impact of ozone levels on daily admissions. The estimated coefficient of O3 is statistically significant at the 1% level. All other pollutants were not significantly associated with the number of daily admissions. Conclusions: Short-term exposure to ozone may be associated with increased psychiatric emergency services admissions. Findings add to previous literature on existing evidence for air pollution to have an impact on mental health. Ozone may be considered a potential environmental risk factor for impaired mental health.